A case report of truncus arteriosus with intact ventricular septum and crossed branch pulmonary arteries. Issue 4 (29th March 2023) - Davidson, Hannah; Seco, Michael; Asakai, Hiroko; Liava'a, Matthew
Abstract: Background: Truncus arteriosus (TA) or persistent arterial trunk describes the presence of a solitary arterial trunk arising from the base of the heart, supported by a common ventriculoarterial junction. The trunk gives rise to the coronary arteries, systemic arteries, and at least one pulmonary artery. Truncus arteriosus is a rare congenital cardiac disease, and even rarer is the absence of ventricular septal defect. Case summary: We report a case of a 2-day-old infant who presented with cyanosis and a cardiac murmur. He was diagnosed with TA with intact ventricular septum (IVS), as well as crossed pulmonary arteries which was identified on pre-operative imaging. We describe the surgical management and short-term follow-up. Discussion: Our clinical case demonstrates a unique diagnosis and management of TA with IVS identified by pre-operative imaging with good surgical outcome.